2012
DOI: 10.1063/1.4765368
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Viscosities of 11 Dilute Gases at 25 °C

Abstract: Commercially manufactured meters that measure the flow of a process gas are often calibrated with a known flow of a surrogate gas. This requires an accurate model of the flow meter and accurate values of the relevant thermophysical properties for both gases. In particular, calibrating a "laminar" flow meter near ambient temperature and pressure requires that the ratio (process gas viscosity)/(surrogate gas viscosity) be known to approximately 0.1%. With this motivation, we critically reviewed measurements of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 52 publications
13
78
0
Order By: Relevance
“…A similar effect was discovered by Berg and Moldover [5] in the data set published by Evers et al [3]. Deviations of the data from Evers et al [3] from the values published by Berg and Moldover [5] are shown in figure 3. Further details concerning figure 3 are discussed below.…”
Section: An Extended Model Function For the Viscosity Measurementsupporting
confidence: 78%
See 3 more Smart Citations
“…A similar effect was discovered by Berg and Moldover [5] in the data set published by Evers et al [3]. Deviations of the data from Evers et al [3] from the values published by Berg and Moldover [5] are shown in figure 3. Further details concerning figure 3 are discussed below.…”
Section: An Extended Model Function For the Viscosity Measurementsupporting
confidence: 78%
“…(2) The FIGURE 3. Relative deviations of the experimental viscosity data of Evers et al [3] and of this work (both extrapolated to zero density) from recommended values published by Berg and Moldover [5] at zero density plotted vs. viscosity. s, Evers et al [3]; 4, This work with experimentally determined residual damping; h, This work with calibrated residual damping.…”
Section: An Extended Model Function For the Viscosity Measurementmentioning
confidence: 85%
See 2 more Smart Citations
“…According to Berg and Moldover [7], the viscosities of dilute gases at 25 C have high accuracy. The values of viscosity and density of argon, carbon dioxide, nitrogen and hydrogen were taken from literature [7][8][9][10][11][12]. The result of the calibration is plotted in Fig.…”
Section: Calibrationmentioning
confidence: 99%